Evaluasi Toleransi 32 Genotipa Hasil Persilangan Padi Gogo Lokal Bengkulu Terhadap Naungan Pada Kebun Kelapa Sawit Muda - Asfaruddin, Asfaruddin; Mulatsih, Sri (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2017)
This research aim is to know the tolerance of 32 genotipes result of crossis of local  Bengkulu upland rice to shade in young oil palm plantion. The research was conducted in Bumi Ayu village of Bengkulu from March to August 2017.The research was conducted using split plot design  with three replication. The main factor is shade consits two level. i.e: (A) with shade and (B) without shade. The subplot is 32 genotipes.The result of research show that shade from oil palm canopy affects to plant heigh, number of productive tillers, panicels long, weigh of 100 grans, and weigh of grans per plots.  Shade causes a decline in growth and yield of upland rice. On this evaluation obtained eleven genotipes are tolerant to shede, i.e:   UNHZ 1, UNHZ 7, UNHZ 12 A, UNHZ 21,   UNHZ 23, UNHZ 24, UNHZ 26,  UNHZ 27, UMHZ 28, UNHZ 29 dan  UNHZ 31.